1996
DOI: 10.1029/96gl01569
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Trace Molecule Spectroscopy (ATMOS) Experiment: Deployment on the ATLAS space shuttle missions

Abstract: determined by a combination of factors: rapid increase in opacity through the troposphere, aerosols and cloud tops obscuring the sun, lack of accuracy in assigning tangent heights and pressures to individual spectra, and the difficulty in retrieving stratospheric constituent volume mixing ratios (vmrs) below their peak concentrations. Issues limiting the lower altitude range will be addressed in future analyses. The data processing and inversion methods employed with the ATMOS data follow those described by No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(124 citation statements)
references
References 27 publications
6
118
0
Order By: Relevance
“…[8] We have checked the new line listing using atmospheric spectra recorded by the ATMOS instrument [Gunson et al, 1996, and references therein]. The modeling of the atmospheric spectra was performed using the ORM (Optimized Retrieval Model) code [Ridolfi et al, 2000] developed for a near real time level 2 analysis of the MIPAS spectra.…”
Section: Discussionmentioning
confidence: 99%
“…[8] We have checked the new line listing using atmospheric spectra recorded by the ATMOS instrument [Gunson et al, 1996, and references therein]. The modeling of the atmospheric spectra was performed using the ORM (Optimized Retrieval Model) code [Ridolfi et al, 2000] developed for a near real time level 2 analysis of the MIPAS spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Bruhl et al [1996] showed agreement between HALOE and correlative measurements that was typically within 5% between 1 and 30 mbar (from $25 to 50 km). Few correlative measurements were available at higher altitudes, but Bruhl et al [1996] showed that HALOE O 3 was generally 20-30% lower than version 2.0 data from the Atmospheric Trace Molecule Spectroscopy (ATMOS) experiment [Gunson et al, 1996;Abrams et al, 1996] near 60 km. We have repeated comparisons between HALOE and ATMOS for the most recent versions of the two data sets (19 and 3.0, respectively, not shown), and still find a bias between them near 60 km, but it is at the 10% level (HALOE < ATMOS).…”
Section: Haloe Datamentioning
confidence: 99%
“…Although general databases such as HITRAN (Rothman et al, 2005) or GEISA (Jacquinet-Husson et al, 2005) existed it was decided at the beginning of the development of the MI-PAS data processing software to generate a dedicated spectroscopic database for MIPAS, as was done for the ATMOS experiment (Gunson et al, 1996), in order to be able to implement the best spectral parameters in the shortest possible time and also to meet the specific needs of MIPAS. The first version "mipas pf2.0" was based on both the 1996 version of HITRAN and on new laboratory spectroscopic data and new calculations (Flaud et al, 2003a;Flaud et al, 2003b).…”
Section: Spectroscopic Database For Mipas Retrievalsmentioning
confidence: 99%